Empathy and recognition of facial expressions of basic and complex emotions, in Medicine students at the State University of Mato Grosso do Sul (Research, Society and Development, 2020)
Objective: To evaluate empathy and the humanistic process in the relationship between medical students and students, who are academics from the first to the fourth year of the medical course at the State University of Mato Grosso do Sul (UEMS). Methods: The study, carried out in a quantitative, observational and cross-sectional way, analyzed 84 volunteer medical students, from the 1st to the 4th year, through applied questionnaires (Jefferson scale, sociodemographic data and Read mind in the eyes). The data were tabulated via Excel 2010 and analyzed using the t-student test with 95% reliability for the three scales. Results: 84 academics accepted to participate voluntarily in the research, filling in properly the IC and the questionnaires. Of this sample, 21.43% belonged to the first, 30.95% to the second, 9.52% to the third and 38.1% to the fourth year. In relation to the Jefferson de Empatia Scale, the average was 84.59 points for the group from the 1st to the 2nd year, and 84.85 points for the group from the 3rd to the 4th year; the female average (N = 43) was 83.91 points and the male (N = 41), 85.56 points. In the Read The Mind In The Eyes instrument, the female average was 26.44 and the male, 25.80. Regarding the year of college, the average was 26.21 for the 1st and 2nd years, and 26.05 for the 3rd and 4th years. Conclusion: It was observed that the degree of empathy between academics from the 1st to the 4th year, as well as between the female and male sex, was not statistically significant.